The Development of Student Station for Drag Polar Testing - Arifianto, Ony; Muhammad, Hari; Sukma Windratih, Pramesthi; Safi’i, Imam (International Journal of Engineering and Technology, 2018)
In order to improve the teaching and learning activities in the flight mechanic subjects, the Aerospace Engineering Program, ITB, is currently developing a flying laboratory, based on a fixed-wing unmanned aerial vehicle (UAV). The development process itself has reached a phase, where both graphical user interface (GUI) and flight testing scenario for drag polar assessment are being developed, Â and evaluated. The evaluation of the GUI is performed by creating a simulated flight testing using X-plane software. Due to the model availability in the X-plane, a Cessna 172 model is used instead of a fixed-wing UAV model. The drag polar test is conducted by trimming the aircraft model in steady symmetric level flight condition using the autopilot provided by X-plane. In the simulated test scenario, the aircraft weights and trim speeds are varied while the altitude and and center of gravity (CG) location are held constant. The flight data is then captured and processed with the developed GUI. Further, the lift coefficient (CL) and drag coefficient (CD) are obtained from the aircraft weight, engine thrust, trim speed, and the corresponding atmospheric data. The coefficients are plotted and a curve fitting process is performed to obtain the analytical approximation of the drag polar curve. When the calculation results are compared to the lift and drag coefficients data of the aircraft model, obtained directly from X-plane software, both of them are in a good agreement. Differences might appear from the incompatibility in the drag components calculation of the X-plane software.Â Â